The Degree of School Administrators’ Employment of Information Technology in Administrative Tasks from the Teachers’ point of view - A Field Study in Public Secondary Schools in Lattakia City - نصر لبنا (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research aimed to identified the degree to which school Administrators employ information technology in general secondary schools from the teachers’ point of view in Lattakia City, and identified differences in teachers’ perspectives are known according to the variables (scientific and educational qualifications, experience years), and to achieve the goal of the research, a questionnaire was designed that included (34) phrases, distributed over three axes: (the school principal’s employment of information technology, encouragement of teachers to use technology, the availability of the physical environment for information technology), which were applied to the research sample consisting of (228) teachers of secondary schools in Lattakia city. The research reached the following results: - The degree of school Administrators’ employment of information technology in administrative tasks in general secondary schools in Lattakia city from the teachers’ point of view is middle.- There is a statistically significant difference between the average teachers’ scores about the degree of school Administrators’ employment of information technology in their schools from due to the academic and educational qualifications in favor of the educational qualification diploma holders, and according to number of years of experience in favor of the experienced (more than 10 years), except for the differences at the axis of the availability of the physical environment for information technology were not significant for him. In light of the results reached by the research, the researcher suggested working to provide a physical environment for information technology in secondary schools, and to set up training courses for managers in the field of information technology and to employ it in administrative tasks in the school.